CD4+RORγt++ and Tregs in a Mouse Model of Diet-Induced Nonalcoholic Steatohepatitis. (1st July 2015) - Vonghia, Luisa; Ruyssers, Nathalie; Schrijvers, Dorien; Pelckmans, Paul; Michielsen, Peter; De Clerck, Luc; Ramon, Albert; Jirillo, Emilio; Ebo, Didier; De Winter, Benedicte; Bridts, Chris; Francque, Sven
Abstract : Background and Aims . Inflammatory mediators that cross-talk in different metabolically active organs are thought to play a crucial role in the pathogenesis of Nonalcoholic Steatohepatitis (NASH). This study was aimed at investigating the CD4+ROR γ t+ T-helper cells and their counterpart, the CD4+CD25+FOXP3+ regulatory T cells in the liver, subcutaneous adipose tissue (SAT), and abdominal adipose tissue (AAT) in a high fat diet (HFD) mouse model. Methods . C57BL6 mice were fed a HFD or a normal diet (ND). Liver enzymes, metabolic parameters, and liver histology were assessed. The expression of CD4+ROR γ t+ cells and regulatory T cells in different organs (blood, liver, AAT, and SAT) were analyzed by flow cytometry. Cytokine and adipokine tissue expression were studied by RT-PCR. Results . Mice fed a HFD developed NASH and metabolic alterations compared to normal diet. CD4+ROR γ t++ cells were significantly increased in the liver and the AAT while an increase of regulatory T cells was observed in the SAT of mice fed HFD compared to ND. Inflammatory cytokines were also upregulated. Conclusions . CD4+ROR γ t++ cells and regulatory T cells are altered in NASH with a site-specific pattern and correlate with the severity of the disease. These site-specific differences are associated with increased cytokine expression.